1974
DOI: 10.1536/ihj.15.84
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin-Induced Excitation of Afferent Cardiac Sympathetic Nerve Fiber

Abstract: SUMMARYThe effect of bradykinin on afferent cardiac sympathetic nerve fibers has been examined. Using anesthetized dogs, the action potentials of the fi bers were derived from either the 2nd or 3rd thoracic communicating ramus of the left side. Excitation of the afferent fibers was observed following administration of bradykinin acetate dissolved in physiological saline on the left ventricular wall. The minimum concentration required for excitation was 50-100ng/ml. The fibers were excited rhythmically synchron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(57 citation statements)
references
References 5 publications
4
52
1
Order By: Relevance
“…Tachyphylaxis has been found to develop in cutaneous mechanoreceptors in cats when bradykinin is administered at 15 min intervals (Beck & Handwerker, 1974). The development of tachyphylaxis to bradykinin was not observed in previous studies of cardiac sympathetic mechanoreceptors (Uchida & Murao, 1974a;Nichi et al 1977), however, and the excitatory nociceptive reflex described by Staszewska-Barczak et al (1976) (1978) found that previous application of low concentrations of prostaglandin El prevented the development of tachyphylaxis when bradykinin was applied to sympathetic afferent endings in the heart, and when a cardiac receptor had become desensitized by repeated applications of bradykinin application of prostaglandin E1 to the receptor site restored the bradykinin response to its initial level. A similar interaction between bradykinin and prostaglandin E has been demonstrated in experiments on cutaneous nociceptors (Handwerker, 1976), and this type of interaction may explain the potentiation observed in reflex experiments.…”
Section: Brad Ykinin and Cardiac Sympathetic Afferents 533mentioning
confidence: 89%
See 3 more Smart Citations
“…Tachyphylaxis has been found to develop in cutaneous mechanoreceptors in cats when bradykinin is administered at 15 min intervals (Beck & Handwerker, 1974). The development of tachyphylaxis to bradykinin was not observed in previous studies of cardiac sympathetic mechanoreceptors (Uchida & Murao, 1974a;Nichi et al 1977), however, and the excitatory nociceptive reflex described by Staszewska-Barczak et al (1976) (1978) found that previous application of low concentrations of prostaglandin El prevented the development of tachyphylaxis when bradykinin was applied to sympathetic afferent endings in the heart, and when a cardiac receptor had become desensitized by repeated applications of bradykinin application of prostaglandin E1 to the receptor site restored the bradykinin response to its initial level. A similar interaction between bradykinin and prostaglandin E has been demonstrated in experiments on cutaneous nociceptors (Handwerker, 1976), and this type of interaction may explain the potentiation observed in reflex experiments.…”
Section: Brad Ykinin and Cardiac Sympathetic Afferents 533mentioning
confidence: 89%
“…We usually applied bradykinin to the tissues in a solution containing 1 #g/ml. because this concentration applied to the epicardium produces the maximum reflex increase in blood pressure (Staszewska-Barezak et al 1976) and also the maximum stimulation of cardiac sympathetic afferent nerves (Uchida & Murao, 1974a). Topical application of bradykinin (1 0 #g/ml.)…”
Section: Generalmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in mammals and pythons, injection of BK leads to a rise in circulating catecholamines, which is released from sympathetic neurons (27,28).…”
Section: Cardiovascular Responses To Bkmentioning
confidence: 99%